D-serine increases adult hippocampal neurogenesis - Sultan, Sebastien; Gebara, Elias G.; Moullec, Kristell; Toni, Nicolas (Frontiers in Neuroscience, 2013)
Adult hippocampal neurogenesis results in the continuous formation of new neurons and is a process of brain plasticity involved in learning and memory. The neurogenic niche regulates the stem cell proliferation and the differentiation and survival of new neurons and a major contributor to the neurogenic niche are astrocytes. Among the molecules secreted by astrocytes, D-serine is an important gliotransmitter and is a co-agonist of the glutamate, N-methyl-D-aspartate (NMDA) receptor. D-serine has been shown to enhance the proliferation of neural stem cells in vitro, but its effect on adult neurogenesis in vivo is unknown. Here, we tested the effect of exogenous administration of D-serine on adult neurogenesis in the mouse dentate gyrus. We found that 1 week of treatment with D-serine increased cell proliferation in vivo and in vitro and increased the density of neural stem cells and transit amplifying progenitors. Furthermore, D-serine increased the survival of newborn neurons. Together, these results indicate that D-serine treatment resulted in the improvement of several steps of adult neurogenesis in vivo.